Outcomes of the environmental streamlining pilot projects. - Bracaglia, Frank (Research results digest (National Cooperative Highway Research Program), 2005)
"This digest presents the results of NCHRP Project 25-24,, "Monitoring, analyzing, and reporting on the environmental streamlining pilot projects." The study was conducted by Vanasse Hangen Brustlin, Inc. the Principal Investigator was Frank Bracaglia."